Rapid myelin water imaging in human cervical spinal cord. Issue 4 (9th November 2016) - Ljungberg, Emil; Vavasour, Irene; Tam, Roger; Yoo, Youngjin; Rauscher, Alexander; Li, David K.B.; Traboulsee, Anthony; MacKay, Alex; Kolind, Shannon
Abstract : Purpose: Myelin water imaging (MWI) using multi‐echo T2 relaxation is a quantitative MRI technique that can be used as an in vivo biomarker for myelin in the central nervous system. MWI using a multi‐echo spin echo sequence currently takes more than 20 min to acquire eight axial slices (5 mm thickness) in the cervical spinal cord, making spinal cord MWI impractical for implementation in clinical studies. Methods: In this study, an accelerated gradient and spin echo sequence (GRASE), previously validated for brain MWI, was adapted for spinal cord MWI. Ten healthy volunteers were scanned with the GRASE sequence (acquisition time 8.5 min) and compared with the multi‐echo spin echo sequence (acquisition time 23.5 min). Results: Using region of interest analysis, myelin estimates obtained from the two sequences were found to be in good agreement (mean difference = −0.0092, 95% confidence interval =  − 0.0092 ± 0.061; regression slope = 1.01, ρ  = 0.9). MWI using GRASE was shown to be highly reproducible with an average coefficient of variation of 6.1%. Conclusion: The results from this study show that MWI can be performed in the cervical spinal cord in less than 10 min, allowing for practical implementation in multimodal clinical studies. Magn Reson Med 78:1482–1487, 2017. © 2016 International Society for Magnetic Resonance in Medicine.